2015
DOI: 10.3389/fmicb.2015.01107
|View full text |Cite
|
Sign up to set email alerts
|

A tail of two phages: genomic and functional analysis of Listeria monocytogenes phages vB_LmoS_188 and vB_LmoS_293 reveal the receptor-binding proteins involved in host specificity

Abstract: The physical characteristics of bacteriophages establish them as viable candidates for downstream development of pathogen detection assays and biocontrol measures. To utilize phages for such purposes, a detailed knowledge of their host interaction mechanisms is a prerequisite. There is currently a wealth of knowledge available concerning Gram-negative phage-host interaction, but little by comparison for Gram-positive phages and Listeria phages in particular. In this research, the lytic spectrum of two recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Listeria phages as previously reported in other studies [42,[49][50][51]. The identified phages in the present study are commonly found in Listeria strains globally and have been associated with the survival evolution and persistence of L. monocytogenes in food-processing facilities [42,52].…”
Section: Discussionsupporting
confidence: 84%
“…Listeria phages as previously reported in other studies [42,[49][50][51]. The identified phages in the present study are commonly found in Listeria strains globally and have been associated with the survival evolution and persistence of L. monocytogenes in food-processing facilities [42,52].…”
Section: Discussionsupporting
confidence: 84%
“…SV 4b/4e specific phages M188 and MC293 are members of the same cluster of temperate phages as A118, A500, and A006, with high conservation of their tail morphogenesis sub-module [ 103 ] ( Figure 2 ). As SV 4b/e specific phages, their RBPs are proposed to require terminal GlcNAc at position C4 of the RhoP backbone for attachment ( Figure 5 ).…”
Section: Wall Teichoic Acid-binding Listeria Pmentioning
confidence: 99%
“…As SV 4b/e specific phages, their RBPs are proposed to require terminal GlcNAc at position C4 of the RhoP backbone for attachment ( Figure 5 ). Continued exposure of both phages to an insensitive SV 4c L. monocytogenes strain generated spontaneous mutants, 188_Mut and 293_Mut, with expanded host ranges including SV 4a and 4c strains as well as SV 4b/e strains [ 103 ]. Sequence analysis of their baseplate encoding genes revealed extensive mutation within gp19 of phage 118_Mut and gp20 of 293_Mut.…”
Section: Wall Teichoic Acid-binding Listeria Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional phage therapy is known as being host-specific, property that is determined by the tropism exhibited by the virion structural proteins to bacterial receptors (pilus, flagella, capsule compounds, membrane proteins, etc.) at adsorption step (Casey et al, 2015;Harvey et al, 2018). This property was also believed to be retained at some degree by the endolysins of phages infecting Gram-positive bacteria (Schmelcher et al, 2012) however, to the best of author's knowledge, there are no systematic in silico studies or experimental testing of hostspecificity at intra-genus level.…”
Section: Introductionmentioning
confidence: 99%